UPACARA NGABEN WARGA PANYUWUNGAN DI DESA ABIANBASE KABUPATEN GIANYAR - Ambarnuari, Mery (PANGKAJA: JURNAL AGAMA HINDU, 2019)
Ngaben ceremony is the cremation for return the physical, soul, and the atman to the initially. Bali has many tradition, and the tradition not always same at the diverent village. The diverent make some tradition so unique, one of the unique tradition is the Ngaben ceremony of Panyuwungan clan at the Abianbase village in Gianyar regency. Based on the data analysis, can be found a fact that Ngaben ceremony are share by three part, the first part is preceremony (determine the best day for doing the ngaben ceremony, prepare the medium, ritual offerings, and pabersihan procession); the second part is the realization of Ngaben ceremony (ngaskara ceremony, ngupadesa ceremony, the cremation, and pengiriman ceremony); The third part is post Ngaben ceremony (pecaruan ceremony).The fungsion of the Ngaben ceremony Panyuwungan clan at Abianbase village is the cultural Fungsion, consist of: social fungtion, economy fungtion, language fungtion, the art fungtion, and religion fungtion.The meaning of the Ngaben ceremony Panyuwungan clan at Abianbase village was teology meaning, eskatology meaning, and soteriology meaning.